Implementation of Prototype Biodigester for the Development of Healthy and Productive Villages through Community Empowerment - Maziyya, Nur; Rahayuwati, Laili; Pramukti, Iqbal; Luthfi, Wazirul; Agustina, Habsyah Saparidah; Ibrahim, Kusman; Lukman, Mamat; Rosidin, Udin; Witdiawati, Witidiawati (Media Karya Kesehatan, 2025)
Waste remains a complex environmental problem, particularly in rural areas that rely heavily on agricultural and livestock activities. This condition requires sustainable technology-based waste management alternatives to prevent deterioration in sanitation quality, contamination of water sources, and the decline of environmental carrying capacity for community life. Compreng Village, located in Subang Regency, is predominantly inhabited by farmers, making it vulnerable to environmental pollution due to inadequate waste management practices.This Community Service Program was implemented by introducing an alternative waste management approach, namely the utilization of a Biodigester prototype for household organic waste and agricultural residue processing. The program was carried out under the theme “Healthy and Productive Village,” in which community members were trained to convert organic waste into a renewable energy source as a complementary alternative to LPG gas, while the resulting bioslurry was processed into compost fertilizer. The implementation methods consisted of four main stages: program socialization, training on waste segregation and biodigester operation, mentoring for organic waste processing practice, and technology transfer through community-based biodigester prototype application. A pre- and post-program knowledge assessment was also conducted using a paired t-test. The evaluation results narratively indicated that community members were able to utilize the biodigester prototype to manage organic waste and use the produced bioslurry as fertilizer. Additionally, the paired t-test results showed a significant increase in knowledge regarding the use of biodigesters for organic waste management (p < .001). As a recommendation, ongoing evaluation and follow-up planning are necessary to ensure the sustainability of this program, so that it may be applied. Keywords: Biodigester, environment, healthy productive village, waste management.